Salvation as Liberation: (Re)Imagining Hope in a Time of Crisis - Douglas, Sally (Uniting Church studies, 2025)
It is not uncommon for people in the Uniting Church to avoid discussion of salvation and to recoil from evangelisation. In part, this occurs because ideas of salvation that focus on sin and atonement are considered questionable, or potentially harmful, by many. This is problematic. The problem is not that people are uncomfortable with a soteriology that focuses on sin and sacrifice. Rather the issue is that people have not been made aware of the diversity of New Testament and early church understandings of salvation. In this paper the soteriological understanding of Jesus’ liberation from cosmic evil will be discussed and investigated for potential resources for responding seriously to the myriad threats to flourishing that face humanity and the earth.